Kajian Literatur Integrasi Aritmetika Sosial dengan Nilai-Nilai Fiqih dalam Zakat pada Pembelajaran Matematika - Putri, Rizqillah Ayunita; Faradiba, Surya Sari (FKIP Universitas Mataram, 2025)
This study aims to examine the integration of social arithmetic with Islamic jurisprudence (fiqh) values, particularly zakat, in mathematics learning. The method used is a systematic literature review (SLR) with five stages: formulating research questions, identifying relevant articles, assessing study quality, summarizing evidence, and interpreting findings. Articles were searched using the keywords